PPARs, Cardiovascular Metabolism, and Function: Near- or Far-from-Equilibrium Pathways - Yves Lecarpentier; Victor Claes; Jean-Louis Hébert (PPAR Research)
Peroxisome proliferator-activated receptors (PPAR α, β/δ and γ) play a key role in metabolic regulatory processes and gene regulation of cellular metabolism, particularly in the cardiovascular system. Moreover, PPARs have various extra metabolic roles, in circadian rhythms, inflammation and oxidative stress. In this review, we focus mainly on the effects of PPARs on some thermodynamic processes, which can behave either near equilibrium, or far-from-equilibrium. New functions of PPARs are reported in the arrhythmogenic right ventricular cardiomyopathy, a human genetic heart disease. It is now possible to link the genetic desmosomal abnormalitiy to the presence of fat in the right ventricle, partly due to an overexpression of PPARγ. Moreover, PPARs are directly or indirectly involved in cellular oscillatory processes such as the Wnt-b-catenin pathway, circadian rhythms of arterial blood pressure and cardiac frequency and glycolysis metabolic pathway. Dysfunction of clock genes and PPARγ may lead to hyperphagia, obesity, metabolic syndrome, myocardial infarction and sudden cardiac death, In pathological conditions, regulatory processes of the cardiovascular system may bifurcate towards new states, such as those encountered in hypertension, type 2 diabetes, and heart failure. Numerous of these oscillatory mechanisms, organized in time and space, behave far from equilibrium and are “dissipative structures”.